Analysis of the Relationship of Nutritional Status and Learning Achievement of Students of IT Madina Junior High School Samarinda 2022 - Tisa Ayu Febriani; Ratnawati; Wiryanto; Nurul Wahdah (Formosa Journal of Science and Technology, 2022)
Learning achievement is generally related to aspects of knowledge while learning outcomes include aspects of student character formation. Factors that can improve learning achievement include students' nutritional status. This study aims to determine the relationship between nutritional status and student achievement at SMP IT Madina Samarinda. This research is an analytic observational study with a cross sectional approach. The research location is SMP IT Madina Samarinda. The population in this study were 138 female students. The sample size in this study was 57 female students who were taken by random sampling. Data processing used univariate and bivariate data analysis. The research results used Kendall's Tau B statistical test with p <0.05. There is no relationship between BMI/U nutritional status and learning achievement p value = 0.894 > α=0.05, there is no relationship between anemia nutritional status and learning achievement p value = 0.671> α=0.05 and there is no relationship between knowledge of anemia and anemia 0.244 >α = 0.05. There is no significant relationship between BMI/U nutritional status and student achievement at SMP IT Madina Samarinda.